(untitled) (Castilla. Estudios de Literatura, 2016)
Even though connetions between two poetic spanish generations as the 27 and 50s have been studied, these researches aren’t the most abundant, especially when it’s about studying an author considered difficult, as it’s the case of Carlos Barral. However the texts of Jorge Guillén’s Cántico influenced in Barral’s Metropolitano, meaning an important relation between two seemingly distant poets. This research will show how both writers poeticize reality in a similar way, although with systematically opposed attitudes: the particular world of Barral is the perfect negative of Guillén’s world. It’ll be analyzed the poetic affinity of the writer from Barcelona for the writer from Valladolid from several views, like their life relationship —in which the role of Jaime Gil de Biedma is essential—, traces of Cántico in Metropolitano and a similar poetic logic. Finally, the fact that Jorge Guillén was the spanish poet of the twentieth century —even of the spanish Literary History— most admired by Carlos Barral will emerge as an evident conclusion.